Agreement between questionnaire report of allergy‐related outcomes in school‐age children and objective measures of atopy: the Saskatchewan rural health study. Issue 8 (August 2015) - Chu, L.; Rennie, D.; Cockcroft, D.; Pahwa, P.; Dosman, J.; Hagel, L.; Karunanayake, C.; Lawson, J.
Summary Background and Objectives In population‐based studies, questionnaires remain the most efficient tool to assess the presence of allergy and atopic conditions, but the quality of the information obtained needs to be validated. We sought to evaluate the agreement and predictive values of a questionnaire to assess atopy in rural children, an understudied population with regard to atopy and allergic disease. Methods A total of 480 schoolchildren (grades 1–8) from rural Saskatchewan completed a questionnaire report of allergy and atopic outcomes and participated in skin prick testing (SPT). SPT for 6 common allergens (local grasses, wheat dust, cat dander, house dust mite mixed, Alternaria, and Cladosporium) was completed. Subjects with at least one positive SPT (≥ 3 mm) compared to the negative control were considered to be atopic. We considered per cent concordance, Kappa, sensitivity, specificity, and the positive predictive value and negative predictive value (NPV, PPV) of reported allergies or allergic conditions in comparison with SPT as the gold standard. Results We found that 25.0% of children reported a history of any allergy and 19.4% were atopic based on SPT. The agreement between questionnaire report of allergic triggers and atopy measured by SPT was high (83.0–89.5%). The agreement between atopy and report of allergic conditions ranged from 67.1% to 79.6%. Individual allergic conditions demonstrated high specificity but low sensitivity. The questionnaire report of any allergy had a low PPV in detecting atopy (47.3%) and high NPV (86.3%). The PPV of reported allergic conditions was low (24.8–43.9%), but the NPV was again high (82.0–82.9%). Conclusions We found that the standardized questionnaire report of allergy and atopic conditions was shown not to efficiently and reliably predict atopy. However, given the good specificity and the NPV, the questionnaire may be an efficient tool for epidemiological studies that involve the differential inclusion of subjects without atopy.